Excavations at Myrmekion in 2006–2013 - Butyagin, Alexander (Hyperboreus, 2015)
A survey of the excavations at Myrmekion (the Northern coast of the Bay of Kerch) conducted by the Myrmekion expedition of the State Hermitage Museum in 2006–2013.